Knowledge and Awareness of Autism Spectrum Disorder Among Teachers in Ekiti State, Nigeria - Benjamin Omolayo; Michael Auta; Elizabeth Akinyemi; Uba Dennis (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2020)
This is an investigation of the knowledge and awareness of Autism Spectrum Disorder among secondary school teachers in Ekiti State, Nigeria. It is a school-based cross-sectional study using a multi-stage sampling method to select local government areas, secondary schools, and participants for the study. A total of 107 teachers selected from 21 secondary schools in 2 local government areas participated in the study. A Survey of Knowledge of Autism Spectrum Disorder (ASK-ASD) was used to assess knowledge while an ordinary awareness questionnaire was used to assess the teachers' awareness of the disorder. Using Pearson correlation coefficient and one-way Analysis of Variance to test five hypotheses, results showed no significant relationship between knowledge of Autism Spectrum Disorder and participants having a family or friend with the disorder (r (105) = -.113 p>.05). Finding also revealed a significant relationship between knowledge of Autism and prior training on Autism (r(107) = -.266 p<.05). Age has a significant influence on knowledge of the disorder (F (2, 98) = 4.29 p<.05) but school type (F (2, 104) = 2.506 p>.05) and teaching experience (F (2,103) = 1.971 p>.05) do not have a significant influence on knowledge of Autism. The result further shows that 96.2% of the participants were aware of the disorder while 3.8% were unaware of it. It was recommended that secondary school teachers be equipped with information about Autism Spectrum Disorder through periodic seminars, workshops, and conferences.